2013
DOI: 10.1111/jnu.12016
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influences of Sexual Risk Among Urban African American Adolescent Males

Abstract: Evidence has shown that African American adolescent males are more likely to engage in high-risk sexual behaviors. Understanding the sexual risk communication between African American adolescent males and their parents is important to developing strategies in reducing sexual risk behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 45 publications
6
63
0
1
Order By: Relevance
“…Conservative/Permissive Sexual Attitudes Nine studies showed that parent-adolescent sexual communication significantly predicted less permissive/more conservative attitudes toward engaging in sex (Cederbaum et al 2013;DiIorio et al 1999;Harris et al 2013;Holman and Kellas 2015;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004;Miller et al 1998;Moore and Davidson 1999;Treboux and Busch-Rossnagel 1995). Seven studies reported mixed findings (i.e., an empirical relation was only found for a meaningful subset of the sample and/or a particular variable of interest), which are detailed as follows.…”
Section: Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative/Permissive Sexual Attitudes Nine studies showed that parent-adolescent sexual communication significantly predicted less permissive/more conservative attitudes toward engaging in sex (Cederbaum et al 2013;DiIorio et al 1999;Harris et al 2013;Holman and Kellas 2015;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004;Miller et al 1998;Moore and Davidson 1999;Treboux and Busch-Rossnagel 1995). Seven studies reported mixed findings (i.e., an empirical relation was only found for a meaningful subset of the sample and/or a particular variable of interest), which are detailed as follows.…”
Section: Attitudesmentioning
confidence: 99%
“…Condom-use and Safe Sex Communication Efficacy Twelve studies reported a significant relation between parent-adolescent sexual communication and adolescents' greater perceived ability to acquire and use condoms or contraceptives (Harris et al 2013;Hutchinson et al 2003;Hutchinson and Cooney 1998;Hutchinson 2010;Kowal and Blinn-Pike 2004;Malcolm et al 2013;Mastro and Zimmer-Gembeck 2015), successfully negotiate the use of condoms with a resistant or new partner (DiClemente et al 2001;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004), and to discuss healthrelated topics such as STDs and AIDS with a current or hypothetical partner (DiIorio et al 2000;Sales et al 2007;Shoop and Davidson 1994). Three studies reported mixed findings: Fletcher et al (2015) found that receiving messages endorsing sex as normative predicted emerging adult women's greater condom-use efficacy, though messages endorsing sex as strictly relational or marital did not; Levin et al (2012) reported that the reception of sex-positive messages positively predicted condom-use and safe-sex communication efficacy in emerging adult men, but not women, and that the reception of abstinence messages predicted a decrease in the same for both emerging adult men and women; Lefkowitz and Espinosa-Hernandez (2007) reported that higher quality parent-adolescent sexual communication predicted fewer perceived barriers to using condoms, but receiving messages pertaining to dating, fertility issues, dangers of sex, and abstinence, were unrelated.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Geri çekme yönteminin genellikle erkeklerin ilk kullandığı yöntem olduğu göz önünde bulundurulduğunda, cinsel sağlık eği-timi kapsamında tüm yöntemleri içine alan bir üreme sağlığı eğitiminin gençlere verilmesinin önemi anlaşılabilir. 16,17 Cinselliğin çiftler arasında ve toplumda rahat bir şekilde konuşulamaması, özellikle ark.n etkisi ile yöntem seçme olasılığını ve geri çekme yönteminin erkeklerin çoğunlukla ilk kullandığı yöntem olmasını beraberinde getirmektedir. 3,13,18 Bu durumda, ilk yöntem seçiminin bir sonraki AP yöntem seçiminde çok önemli olduğu görünmektedir.…”
Section: Discussionunclassified
“…Social, emotional and psychological development is incomplete, so they tend to experience forms of dangerous behavior that can lead to serious consequences [8]- [10].…”
Section: Introductionmentioning
confidence: 99%